PENINGKATAN KEMAMPUAN MENYAJIKAN TEKS DISKUSI SISWA SMP NEGERI 11 BINTAN MELALUI PEMANFAATAN "ASAM PEDAS" - Aprilyana, Selly (Jurnal Pembelajaran Prospektif, 2025)
The purpose of this study was to improve students' ability to present discussion texts by utilizing "ASAM PEDAS". To improve students' abilities, the researcher designed a new learning innovation that the author called "ASAM PEDAS" (Aplikasi Anak Melayu Pembelajaran Diskusi Asyik). This special application consists of webex as a space for implementing presentations and discussion processes. Canva for making flyers to inform what material will be presented, the implementation schedule, and the discussion implementer. Google form to create online attendance, and barcode studio to create QR codes to make it easier for participants to enter the room. Teacher features to upload questions and student features to answer assignments given by the teacher. To determine the level of student ability, the researcher conducted classroom action research planned in 2 cycles. The sample of this study was 29 students of class IXC SMP Negeri 11 Bintan. The results of the study showed that "ASAM PEDAS" can improve students' ability to present discussion texts. This can be seen from the average value of students' initial abilities from 64.07 to 72.17 in cycle I and increasing to 87.55 in cycle II. This shows that "ASAM PEDAS" is able to improve students"™ ability to present discussion texts because it is easy to use and the discussion implementation process is unique.